2017
DOI: 10.1371/journal.pone.0175690
|View full text |Cite
|
Sign up to set email alerts
|

Childhood socioeconomic status and childhood maltreatment: Distinct associations with brain structure

Abstract: The present study examined the relationship between childhood socioeconomic status (SES), childhood maltreatment, and the volumes of the hippocampus and amygdala between the ages of 25 and 36 years. Previous work has linked both low SES and maltreatment with reduced hippocampal volume in childhood, an effect attributed to childhood stress. In 46 adult subjects, only childhood maltreatment, and not childhood SES, predicted hippocampal volume in regression analyses, with greater maltreatment associated with lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
53
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(59 citation statements)
references
References 42 publications
4
53
0
2
Order By: Relevance
“…Another study examined the relationship between brain volumes and current and childhood negative interpersonal events, and current and childhood socioeconomic status (SES). In males, but not females, childhood SES was marginally related to left hippocampal volumes and higher adversity associated with higher right amygdala volume in females and with lower right amygdala volume in males [50•]. However, this study also found gray matter surplus among females, with higher adversity associated with higher right amygdala volume in females and with lower right amygdala volume in males.…”
Section: Direct Evidence Of Sex Differences In Trauma-related Psychopmentioning
confidence: 61%
See 2 more Smart Citations
“…Another study examined the relationship between brain volumes and current and childhood negative interpersonal events, and current and childhood socioeconomic status (SES). In males, but not females, childhood SES was marginally related to left hippocampal volumes and higher adversity associated with higher right amygdala volume in females and with lower right amygdala volume in males [50•]. However, this study also found gray matter surplus among females, with higher adversity associated with higher right amygdala volume in females and with lower right amygdala volume in males.…”
Section: Direct Evidence Of Sex Differences In Trauma-related Psychopmentioning
confidence: 61%
“…All manuscripts employed MRI imaging methods but one, which employed PET. Of these, five [47•, 48, 49, 50•, 51] used structural imaging only, four of which included only gray matter volumetrics and one also employed diffusion tensor imaging (DTI) for structural connectivity. Of the eight remaining studies, which used functional imaging, one [52•] employed resting state functional connectivity (rs-FC) analyses as well as DTI, and six studies [53•, 54•, 55•, 56•, 57•, 58•] employed task-bound functional MRI (fMRI).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lawson, Camins, et al. () and Lawson, Hook, et al. () recently conducted a meta‐analysis of the impact of SES on executive functions and found mixed results and only a medium effects size.…”
Section: Introductionmentioning
confidence: 99%
“…However, our goal is to understand how SES across a wide income range impacts WM, not how the biological embedding of stress impacts WM. A critical distinction is that stress and enrichment act through different mechanisms to shape development (Amso & Lynn, ; Conger & Donnellan, ; Johnson et al., ; Lawson, Camins, et al., ; Lawson, Hook, et al., ; McLaughlin & Sheridan, ; McLaughlin et al., ; Sheridan, Peverill, Finn, & McLaughlin, ; Ursache & Noble, ) . When incorporating the adversities more common in poverty, there is little doubt that stresses acts to shape outcomes.…”
Section: Introductionmentioning
confidence: 99%